Potensi dan Kendala Pengembangan Angkutan Umum Pariwisata Kawasan Toba - Amrizal Amrizal (Jurnal Teknik Sipil Unaya, 2018)
In the absence of a decent, efficient and economical public transportation service, it can be an obstacle for people, especially tourists, to be able to access their desired goals. Of course this will leave a less pleasant impression for tourists, which potentially reduces the attractiveness of tourists Toba Region which indirectly affect the income of the government and also the people of the tourism sector. Based on these considerations, it is time for both central and regional governments to develop tourist public transportation in Toba and surrounding areas more seriously to improve accessibility and mobility and affordability of travel costs in the region. This can be done by revitalizing the existing public transportation route to be transformed into a public transport route. Based on survey results of public transport users for tourist destinations the number is relatively moderate ie between 2-55% of the total passengers transported at the time of the survey. Recorded only from the Terminal shadow Simpang Pos to Brastagi City, Tongging and Paropo and Terminal Siantar to Parapat, Sidamanik and Tiga Ras indicating the existence of passengers with tourist destination. Based on survey results, only public transportation to Berastagi has Load Factor above 100% that is 124%, so it needs to increase the number of its fleet from 18 units to 24 units. Aspects of public transport services assessed include: travel time, waiting time, ease of getting tickets, seat availability, seating comfort and freedom of movement, stopping / terminals, security during travel, travel safety, route info / public transportation routes and complaint media / complaints about service. The survey was conducted on 255 respondents with the aim to see the perception of passengers on public transport services. From the general survey results for all aspects of public transport services assessed, the perception of passengers on public transport services / tours is still in the good category of 49.29%. However, it does not mean that public transport services / tours that are all there are good because passengers who assess public transport services / tours bad and very bad is also quite a lot in the average that is 1.76% and 7.41%.